PERBEDAAN MOTIVASI BELAJAR IPS PADA MODEL PEMBELAJARAN CTL DAN EKSPOSITORI SISWA SEKOLAH DASAR - Elpri Darta Putra; Siti Quratul Ain; Eva Astuti Mulyani; Mitha Anggriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the difference of students’ learning motivation on CTL learning model and expository learning model. The implementation of CTL and expository learning model was proved to give different effect on the students’ motivation in learning social science subject. This study was quasi-experimental research which did not use a control group. The design of this study was nonequivalent groups pre-test-post-test design. This study was conducted at grade IV SDN 191 Pekanbaru with a total of 45 students. Different learning models significantly influenced the students’ motivation in learning social science. This difference was seen from the average value of the students’ learning motivation in which the average value for expository learning model was 52.72 and the value for CTL model was 79.69. This study also found that the difference value of expository learning model and CTL model towards the students’ motivation was  24.53% while the remaining 74.57% was influenced by other variables.